ТАЪЛИМ СИФАТИ МЕНЕЖМЕНТИНИНГ ТАШҚИ ВА ИЧКИ НАЗОРАТ МЕХАНИЗМЛАРИ - Юлдашев, М. (SCIENCE and SOCIETY, 2016)
The article deals with the analytical ideas and views on the possibility of using internal and external monitoring of quality management used abroad, in assessing the quality of education in the training of public education personnel in our country.
Keywords: quality of education; quality management; control; external; internal; monitoring of quality; education; programme; methods of teaching; stages of teaching; educational-methodical supply